Development and Evaluation of Amlodipine-Polymer Nanocomposites Using Response Surface Methodology - Zain Alabden Ghanim Ahmed; Samer Hasan Hussein-Al-Ali; Ibrahim Abdel Aziz Ibrahim; Mike Kh. Haddad; Dalia Khalil Ali; Anwar Mahmoud Hussein; Ahmad Adnan Abu Sharar (International Journal of Polymer Science)
Introduction. Polymer nanoparticles are a key tool to deliver drugs to specific sites and to increase drug bioavailability. Aim. This research aims to use poly amide-disulfide nanoparticles as drug delivery systems. Method. Amlodipine (Amlop) was used as a model, forming Amlop-polymer nanocomposites. In this work, we investigated the effect of independent variables (polymer, Fe3+, Al3+, and pH) on the dependent variables (loading efficiency (%LE), zeta potential, and particle size). Nanocomposites were prepared by an inotropic method. Nanocomposites were characterized by powder X-ray diffraction (PXRD), field emission scanning electron microscopy (FE-SEM), Fourier transform infrared spectroscopy (FTIR), and a release study. Results. From the XRD data, the Amlop-polymer nanocomposite shows semi crystallinity. In addition, the disappearance of drug peaks indicates that the drug was incorporated between the polymer molecules and was amorphous in behavior. The FTIR for the nanocomposite shows the functional group of the drug, which indicates the incorporation of Amlop into the nanocomposite. From FE-SEM, the results showed that our nanocomposites have an average particle size of approximately 130 nm. The release of amlodipine from the Amlop-polymer nanocomposite was found to be controlled, with approximately 85% within approximately 24 hours. Conclusion. The amide-disulfide polymer nanoparticles are promising carriers for different types of drugs.